Effect of Laser Irradiation with 532 nm Wavelength on The Optical Properties of PVA/MR Solutions (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background: This work aims to study the impact of 532 nm laser irradiating on the optical properties of the Polyvinyl alcohol/ Methyl Red (PVA/MR) solution before and after laser irradiation  32mW with various times (0, 20, 30 and 40) minutes. Materials and Methods:The polymer (PVA) powder 500 mg was dissolved in 50 ml distilled water at temperature 80 ˚C and the methyl red (MR) 30 mg was dissolved in 10 ml at temperature 80 ˚C using solution dilution formula  . A semiconductor laser with a wavelength of 532 nanometers was used to irradiate the solution. Results:The absorbance, reflectance, and transmittance spectrum of solution prior to and following laser irradiation were recorded. Then, the optical constants and energy gap were calculated. Conclusions:The irradiation with the 532nm laser leads to a break of the bonds (From the absorbance spectrum, it decreases as the irradiation time increases. This indicates the breaking of bonds.) that results in an increase in the transmittance spectrum, and the energy gap.